2012
DOI: 10.1038/cgt.2011.86
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated p53 expression activates apoptotic pathways in wild-type p53-bearing mesothelioma and enhances cytotoxicity of cisplatin and pemetrexed

Abstract: The majority of malignant mesothelioma possesses the wild-type p53 gene with a homologous deletion of the INK4A/ARF locus containing the p14 ARF and the p16 INK4A genes. We examined whether forced expression of p53 inhibited growth of mesothelioma cells and produced anti-tumor effects by a combination of cisplatin (CDDP) or pemetrexed (PEM), the first-line drugs for mesothelioma treatments. Transduction of mesothelioma cells with adenoviruses bearing the p53 gene (Ad-p53) induced phosphorylation of p53, upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…CDDP is one of such agents and augmented p53 levels in target tumors facilitate CDDP-induced cell death [19], [20]. In fact our previous study showed that Ad-p53-transduced MSTO-211H cells produced synergistic cytotoxicity with CDDP, and that the CI values were below 1 between 0.2 and 0.8 Fa points [21]. The present study demonstrated that combination of ZOL and CDDP produced synergistic or additive anti-tumor effects on mesothelioma with the wild-type p53 gene.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CDDP is one of such agents and augmented p53 levels in target tumors facilitate CDDP-induced cell death [19], [20]. In fact our previous study showed that Ad-p53-transduced MSTO-211H cells produced synergistic cytotoxicity with CDDP, and that the CI values were below 1 between 0.2 and 0.8 Fa points [21]. The present study demonstrated that combination of ZOL and CDDP produced synergistic or additive anti-tumor effects on mesothelioma with the wild-type p53 gene.…”
Section: Discussionmentioning
confidence: 98%
“…Intrapleural injections of Ad-p53 were in fact conducted safely in patients with pleural effusions [28]. Previous studies demonstrated that Ad-p53 activated the p53 pathways and achieved combinatory anti-tumor effects with an anti-cancer agent including CDDP [21], [29], [30]. The mechanism of ZOL-mediated p53 induction remains unclear but the p53-inducible p21 is a downstream target of Ras and RhoA, the major molecules of small G proteins [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al analyzed the effects of Ad-p53 transduction in p14 / p16 -defective mesothelioma [19], which is a direct way to reactivate the p53 pathways. Transduction with Ad-53 induced phosphorylation of p53 at serine 15 and 46 residues, a marker of the p53 activation, and augmented extrinsic apoptotic pathways through upregulating the death receptors.…”
Section: Gene Therapy Targeting Genetic and Signal Pathwaysmentioning
confidence: 99%
“…In contrast, deficiency of p16 augmented phosphorylation of pRb and induced uninhibited cell growth. Increased p53 levels also inhibited the pRb phosphorylation through induction of p21, one of the p53 target molecules [16]. Consequently, up-regulation of p53 is a therapeutic strategy for mesothelioma by enhancing the downstream pathways and inhibiting cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%